2012
DOI: 10.1021/jf3038264
|View full text |Cite
|
Sign up to set email alerts
|

Influence of γ-Radiation on the Structure and Function of Soybean Trypsin Inhibitor

Abstract: Soybean trypsin inhibitor (STI) is a known antinutrient and food allergen present in soybean. γ-Radiation has the potential to inactivate the TI protein. However, a systematic study on the influence of different moisture levels during γ radiation on structure and function of the molecule has not been reported. Pure STI was irradiated up to 200 kGy, in dry state, with 50% moisture and in aqueous solution. The radiation damage in molecular structure was assessed using, SDS-PAGE, size exclusion chromatography, fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…18 Furthermore, Mallikarjunan et al also demonstrated the inuence of g-radiation on the structure and function of soybean trypsin inhibitor. 19 Taken together, these results support the application potential of food constituents as radiosensitizers in radiotherapy.…”
Section: Introductionsupporting
confidence: 54%
“…18 Furthermore, Mallikarjunan et al also demonstrated the inuence of g-radiation on the structure and function of soybean trypsin inhibitor. 19 Taken together, these results support the application potential of food constituents as radiosensitizers in radiotherapy.…”
Section: Introductionsupporting
confidence: 54%
“…Many researchers have also described similar results in concanavalin A and the soybean trypsin inhibitor. 30,31 In addition, irradiation resulted in important changes in the α-La tertiary structure as demonstrated by UV and fluorescence spectroscopy. The UV spectra of the native α-La reflected the maximum absorption peak at around 280 nm, indicating that the UV absorption spectrum of α-La was mainly dependent on tyrosine (Tyr) and tryptophan (Trp) residue sidechain groups.…”
Section: Discussionmentioning
confidence: 99%
“…Gaber (2005) [28] found that -irradiation changed the ordered structure of proteins to the denature form. Mallikarjunan et al [29] reported that irradiation at doses up to 100 kGy in a dry state exhibited a loss in trypsin inhibitor activity through a diminished intensity band of the protein and without the appearance of any fragmented or cross-linked products. Furthermore, the diminished trypsin-inhibitor activity in irradiated rice bran might be attributed to the breakdown of disulfide bonds [30].…”
Section: Resultsmentioning
confidence: 99%